The reflexes of HIV in the life of the seropositive young person (Research, Society and Development, 2021)
Objective: To understand the impact of HIV / AIDS in the lives of HIV positive young people. Methodology: Qualitative, descriptive and exploratory research carried out with 11 young people attended at an outpatient clinic specialized in adolescent health. A semi-structured interview was used as a data collection instrument based on questions in order to outline the profile of young people, as well as to address experiences lived after the diagnosis of the disease. The data were analyzed and grouped into three thematic categories, being discussed in the light of scholars linked to the theme. Results: It was understood about the feelings that the diagnosis of HIV / AIDS brings to the lives of young people, especially due to the association of the disease with death and prejudice. Conclusion: This study made it possible to elucidate the question that, in order to work with HIV-positive young people in the health area, it is necessary for nurses to strengthen the bond with users, promoting an effective reception, using sensitivity and empathy to reduce the unpleasant effects on of the disease and mitigate the suffering during the treatment and follow-up of the young person.